N9-substituted derivatives of kinetin: effective anti-senescence agents - Mik, Václav; Szüčová, Lucie; Smehilová, Mária; Zatloukal, Marek; Doležal, Karel; Nisler, Jaroslav; Grúz, Jiří; Galuszka, Petr; Strnad, Miroslav; Spíchal, Lukáš (Phytochemistry, 2011)
The first isolated cytokinin, 6-furfurylaminopurine (kinetin or Kin), was identified almost 55years ago. Its biological effects on plant cells and tissues include influences on such processes as gene expression, cell cycle, chloroplast development, chlorophyll biosynthesis, stimulation of vascular development, delay of senescence, and mobilization of nutrients. In the present study we prepared a series of eight N9-substituted Kin derivatives, and characterized them with available physicochemical methods such as CI+ mass spectrometry and (1)H NMR spectroscopy. All compounds were tested in three classical cytokinin bioassays: a tobacco callus assay, an Amaranthus assay, and a senescence assay with excised wheat leaves. The ability of the compounds to interact with Arabidopsis cytokinin receptors CRE1/AHK4 and AHK3 was tested in a bacterial receptor assay. Prepared derivatives with certain substitutions of the N9-atom of the purine moiety enhanced the cytokinin activity of the parent compound in the bioassays to a remarkable degree but negatively affected its perception by CRE1/AHK4 and AHK3. The ability of compounds to delay the senescence of excised wheat leaves in both dark and light conditions, was highly correlated with their ability to influence membrane lipid peroxidation, which is a typical symptom of senescence. Our results were corroborated by gene expression profiling of those genes involved in cytokinin metabolism and perception, plant senescence, and the stress response, and suggest that prepared kinetin derivatives might be used as potent anti-senescence agents.
Keywords: nukleární magnetická rezonance biomolekulární; Aging; Triticum; Molecular Structure; puriny; molekulární struktura; kinetin; Nicotiana; tabák; Purines; Nuclear Magnetic Resonance, Biomolecular; Arabidopsis; Kinetin; stárnutí; pšenice; proteiny huseníčku; Arabidopsis Proteins